1996
DOI: 10.1016/0735-1097(96)00156-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral propafenone on defibrillation and pacing thresholds in patients receiving implantable cardioverter-defibrillators

Abstract: Short-term oral propafenone (450 and 675 mg/day) does not significantly affect defibrillation or pacing thresholds. Concomitant use of propafenone in patients with implantable cardioverter-defibrillators with recurrent ventricular or atrial tachyarrhythmias should not interfere with proper device function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…40,41 Similarly, loss of atrial capture has been reported with amiodarone, 42 whereas no such effect was seen on ventricular pacing thresholds. 43 All of these studies were observational in nature.…”
Section: Pacing Thresholdmentioning
confidence: 97%
“…40,41 Similarly, loss of atrial capture has been reported with amiodarone, 42 whereas no such effect was seen on ventricular pacing thresholds. 43 All of these studies were observational in nature.…”
Section: Pacing Thresholdmentioning
confidence: 97%
“…A lidocaína, um dos agentes antiarrítmicos mais extensamente estudado, eleva os limiares de desfibrilação ventricular, de acordo com a maioria dos estudos realizados [6][7][8][9] ; curiosamente, em uma série conduzida por Ujhelyi e cols., esse efeito só foi observado com a utilização de choques monofási-cos, desaparecendo quando da utilização de choques bifá-sicos 34 . A propafenona, uma droga da classe I, mas com ações de classe II e IV discretas, não aparenta alterar os limiares de desfibrilação, sendo entretanto um fármaco pouco estudado 17 . Os efeitos dos betabloqueadores sobre a desfibrilação ventricular parecem ser variáveis, de acordo com o tipo de droga utilizada.…”
Section: Drogas Antiarrítmicas E Limiares De Desfibrilaçãounclassified
“…Patienten, deren Anderung der antiarrhythmischen Medikation einen Anstieg der DFT erwarten lieB (Weglassen von Sotalol, neue Gabe von Amiodaron (70) bzw. neue Gabe von Propafenon (106,131); n = 4), wurden mit einem Dreieck gekennzeichnet, bei einer zu erwartenden Absenkung der DFT (neue Gabe von Sotalol (33); n = 6) wurde ein Quadrat gew/ihlt (149). Die Impulsdauer, fª die bei einem rechtwinkligen Stimulationsimpuls die geringste Energie ben6tigt wurde, war die Chronaxie -eine Zeitkonstante des erregbaren Gewebes (84).…”
Section: Stabilit~it Der Defibrillationsschwelleunclassified